PENINGKATAN KOMPETENSI GAMBAR TEKNIK DOSEN VOKASI MELALUI SERTIFIKASI CERTIFIED SOLIDWORKS ASSOCIATE (CSWA) - Nurtanto, Muhammad; Jandri Fan HT Saragi; Alang Sunding; Iman Mujiarto (Dharma: Jurnal Pengabdian Masyarakat, 2025)
The development of technical drawing competencies for vocational lecturers is an urgent need in meeting the increasingly complex demands of the industry, particularly in the use of design software such as SolidWorks. This development program is supported by the Ministry of Education and Culture through the Vocational Lecturer Competency Development Program (NDPKD), which offers training and certification for the Certified SolidWorks Associate (CSWA). The training was held at the Surabaya State Shipbuilding Polytechnic and involved 20 lecturers from various polytechnics across Indonesia. The program spanned four days and concluded with an international certification exam on the fifth day. The implementation method included simulations, hands-on practice in part and assembly creation, and the CSWA competency test. Training results demonstrated that all participants successfully obtained certification, achieving scores ranging from 175 to 240, highlighting the program’s effectiveness in enhancing lecturers’ competencies. This success not only provides professional recognition for the lecturers but also boosts confidence in applying these skills within classroom instruction. The CSWA training serves as a significant solution for lecturers to integrate technical design skills aligned with industry standards and drive improvements in the university's Key Performance Indicators (KPIs).